Composite current collector containing PTC material and preparation method thereof
By modifying polypropylene and nanobarium titanate, the bonding force between the base film and the metal layer in the composite fluid is enhanced, and the UV resistance and flame retardancy are improved. The problems of insufficient binding force, poor UV resistance and poor flame retardancy in the existing composite fluid are solved, and better thermal runaway performance is achieved.
Patent Information
- Application Number
- CN202411688465.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Among the existing composite fluids, the binding force between the polypropylene base film and the metal layer is insufficient, the ultraviolet resistance is poor, the flame retardancy is poor, and the nanobarium titanate is prone to agglomeration, which affects its use in the base film.
By modifying polypropylene and nanobarium titanate, benzotriazole and thiophene ring/DOPO were introduced respectively to enhance the binding force of the base film and the metal layer, improve the resistance to UV and flame retardancy, and reduce the agglomeration of nanobarium titanate through modification treatment.
It significantly improves the adhesion, UV resistance and flame retardancy of the composite fluid collection, enhances its thermal runaway performance, and reduces the fire risk of the battery during use.
Smart Images

Figure BDA0005150260900000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of current collectors, and in particular to a composite current collector containing a PTC material and a preparation method thereof. Background Art
[0002] The composite current collector is a sandwich structure of "metal conductive layer-polymer material-metal conductive layer". It uses polymer insulating materials such as PET / PP / PI as the "sandwich" layer, i.e., the base film, and deposits metal aluminum or copper on the upper and lower surfaces of the base film. The base film has insulation and flame retardant properties, while the metal conductive layer is relatively thin. It will blow like a fuse in the event of a short circuit and melt quickly before thermal runaway. Battery damage is limited to the puncture site to form a "point break", effectively forming a "circuit-breaking effect", preventing continuous high current from causing battery overheating, and effectively solving safety issues. Therefore, the performance of the base film is the key to determining the quality of the composite current collector.
[0003] Among the many composite current collectors with polymer materials as the base film, composite current collectors with polypropylene as the base film are more common. However, the molecular chain of polypropylene has a small polarity and low surface tension, and the bonding force between it and the metal layer with high surface tension is poor. In addition, polypropylene has poor UV resistance and is prone to aging and degradation after exposure to ultraviolet rays, which has an adverse effect on the performance of the base film. In order to reduce the risk of fire, flame retardants are usually added directly to the base film to improve the flame retardancy. The directly added flame retardant has poor compatibility with polypropylene and is easy to seep out from the base film material, resulting in poor flame retardancy of the base film.
[0004] However, for batteries with higher density, if a short circuit occurs during the puncture or extrusion test, it will be accompanied by a sharp increase in the clockwise current, thereby increasing the risk of thermal runaway and causing safety accidents. In the prior art, materials with a positive temperature coefficient (PTC) such as barium titanate are used. The PTC material exhibits uniform conductivity at the normal operating temperature of the battery, and when the temperature in the battery increases, the resistance of the positive temperature coefficient material suddenly increases to interrupt the flow of current, thereby avoiding the increased risk of thermal runaway. Nano-barium titanate has the characteristics of small particle size and high surface activity, and is easy to agglomerate, so its use in base films is limited.
[0005] Therefore, it is necessary to develop a suitable modification method to improve the bonding strength between the polypropylene base film and the metal, enhance the UV resistance and flame retardancy of the polypropylene base film, add nano-barium titanate with improved agglomeration phenomenon to the polypropylene base film, and then use the base film in the preparation of composite current collectors to obtain composite current collectors with better performance, which is of practical significance. Summary of the invention
[0006] In order to solve the technical problem, the present invention provides a composite current collector containing a PTC material and a preparation method thereof.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A composite current collector containing a PTC material, comprising a polymer base film and copper metal layers located on the upper and lower surfaces of the polymer base film;
[0009] The polymer-based film comprises the following raw materials in parts by weight: 100-110 parts of modified polypropylene, 20-25 parts of modified PTC material, 1.2-1.4 parts of lubricant, 0.3-0.5 parts of initiator, and 14-18 parts of filler;
[0010] The lubricant is selected from one of butyl stearate and ethylene bisstearamide; the initiator is dicumyl peroxide; the filler is alkali-free glass fiber;
[0011] The preparation of the composite current collector containing the PTC material comprises the following steps:
[0012] Step S1, stirring the modified polypropylene, modified PTC material, lubricant, initiator and filler for 30-40 minutes, extruding through a twin-screw extruder at 220-240° C., stretching at 115-125° C., heat-setting at 230-240° C. to form a film, then soaking in distilled water at 55-65° C. for 10-11 hours, and finally drying at 90-100° C. for 6-8 hours to obtain a polymer base film;
[0013] Step S2, using a vacuum evaporation method, passing the polymer base film through a copper plating roller along the axial direction of the copper plating roller, and coating the evaporated metal copper on both sides of the polymer base film to obtain a composite current collector containing a PTC material;
[0014] Further, the copper plating roller has a first temperature zone and a second temperature zone, the temperature of the first temperature zone is 45-55°C, and the temperature of the second temperature zone is 15-25°C;
[0015] The modified polypropylene is prepared by the following steps:
[0016] Step A1, add a carboxylic acid containing a terminal carbon-carbon double bond to DMF, add dichlorothionyl under stirring, reflux and stir at 40-50° C. for 4-5 hours to obtain an acyl chloride product; then add nitro-containing benzotriazole and potassium carbonate to dimethyl sulfoxide to obtain a mixed solution 1, and then add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution 2, and add the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath. After the dropwise addition is completed, the temperature is raised to 40-45° C., stirred at a constant temperature for 8-10 hours, and distilled under reduced pressure to obtain a nitro product;
[0017] Furthermore, the amount ratio of the carboxylic acid containing a terminal carbon-carbon double bond, DMF, and dimethyl sulfoxide is 0.1-0.12 mol: 50-60 mL: 0.12-0.15 mol, the carboxylic acid containing a terminal carbon-carbon double bond is selected from one of 7-octenoic acid, 5-methylhexyl-2-butenoic acid, and 5-hexenoic acid; the amount ratio of nitro-containing benzotriazole, potassium carbonate, and dimethyl sulfoxide is 0.1-0.15 mol: 0.02 -0.04mol:40-50mL, the nitro-containing benzotriazole is selected from 6-methyl-7-nitro-1H-benzo[D][1,2,3]triazole and 4-nitro-1H-1,2,3-benzotriazole; the amount ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution 2 is 13-16g:30-40mL; the amount ratio of the mixed solution 1 and the mixed solution 2 is 50-60mL:40-50mL;
[0018] During the reaction of step A1, a carboxylic acid containing a terminal carbon-carbon double bond reacts with thionyl chloride to generate an acyl chloride product; the acyl chloride product then reacts with a secondary amino group of a nitro-containing benzotriazole to generate a nitro product;
[0019] Step A2, adding the nitro product to ethyl acetate, heating to 45-55°C, starting reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 1-1.5h to obtain a primary amine product;
[0020] Further, the usage ratio of the nitro product, ethyl acetate, and sodium dithionite is 32-36 g: 100-110 mL: 18-20 g;
[0021] During the reaction of step A2, the nitro group in the nitro product is reduced to an amino group to obtain a primary amine product;
[0022] Step A3, adding epichlorohydrin, primary amine product and tetrabutylammonium bromide to toluene, reflux and stir at 100-110° C. for 3-4 hours, adding sodium hydroxide solution after cooling to room temperature, and stirring for 5-6 hours to obtain a functional product;
[0023] Furthermore, the dosage ratio of epichlorohydrin, primary amine product, tetrabutylammonium bromide, toluene, and sodium hydroxide solution is 19-21 g: 35-39 g: 0.05-0.08 mol: 90-100 mL: 20-25 mL; the mass fraction of the sodium hydroxide solution is 40-50%;
[0024] During the reaction of step A3, the amino group of the primary amine product is ring-opened and then ring-closed with epichlorohydrin to form two epoxy groups, thereby obtaining a functional product containing a terminal carbon-carbon double bond, benzotriazole and an epoxy group;
[0025] Step A4: In a protective gas atmosphere, add the functional product and the cross-linking agent to toluene, stir for 10-15 minutes, add polypropylene and continue stirring for 10-15 minutes, seal the reaction bottle, and then 60 After irradiation with Coγ-rays for 8-10 hours, the product is taken out, washed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene;
[0026] Further, the dosage ratio of toluene, functional product, cross-linking agent, and polypropylene is 450-500 mL: 40-50 g: 7-9 g: 130-140 g, and the cross-linking agent is divinylbenzene;
[0027] During the reaction of step A4, 60 Under the irradiation of Coγ-rays and the assistance of a cross-linking agent, the functional product is grafted onto polypropylene to obtain modified polypropylene;
[0028] The preparation of the modified PTC material comprises the following steps:
[0029] Step B1, adding an amino-containing silane coupling agent to ethanol and deionized water, stirring for 8-10 hours to obtain a hydrolyzate; then adding nano-barium titanate to ethanol, ultrasonically dispersing for 20-30 minutes to obtain a dispersion; heating to 60-70° C., adding the hydrolyzate dropwise to the dispersion under ultrasound, stirring for reaction for 10-11 hours, and then drying and grinding into powder to obtain nano-barium titanate containing amino groups on the surface;
[0030] Furthermore, the amount ratio of the amino-containing silane coupling agent, ethanol and deionized water in the hydrolyzate is 10-12g:60-70mL:35-45mL, and the amino-containing silane coupling agent is selected from one of KH-550, KH-540, N-methyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltrimethoxysilane; the amount ratio of nano-barium titanate and ethanol in the dispersion is 5-6g:100-120mL; the amount ratio of the hydrolyzate and the dispersion is 40-50mL:115-125mL; the volume fraction of ethanol is 95%;
[0031] During the reaction of step B1, the amino-containing silane coupling agent is hydrolyzed to form a chemical bond with the surface of the nano-barium titanate to obtain the nano-barium titanate with amino groups on the surface;
[0032] Step B2, in a protective gas atmosphere, add formaldehyde containing a thiophene ring to acetic anhydride, then add potassium carbonate, reflux and stir at 150-170° C. for 24-26 hours, extract, rotary evaporate, and dry to obtain an unsaturated carboxylic acid; in a protective gas atmosphere, add DOPO and the unsaturated carboxylic acid to DMF, stir and react at 90-110° C. for 8-10 hours, cool to room temperature, recrystallize in an ice-water bath, and filter under reduced pressure to obtain a carboxyl product;
[0033] Further, the dosage ratio of formaldehyde containing thiophene ring, acetic anhydride and potassium carbonate is 0.1-0.15 mol: 0.05-0.07 mol: 5-8 mmol, the formaldehyde containing thiophene ring is selected from 2-thiophene carboxaldehyde, 2,2-bithiophene-5-acetaldehyde, 5-isobutylthiophene-2-carboxaldehyde; the dosage ratio of DOPO, unsaturated carboxylic acid and DMF is 23-27 g: 16-22 g: 80-100 mL;
[0034] During the reaction of step B2, the aldehyde group of the formaldehyde containing a thiophene ring reacts with acetic anhydride to generate a carboxylic acid containing a carbon-carbon double bond, i.e., an unsaturated carboxylic acid; DOPO adds to the carbon-carbon double bond of the unsaturated carboxylic acid to obtain a carboxyl product;
[0035] Step B3, adding the carboxyl product to DMF, adding dichlorothionyl under stirring, reflux stirring and reacting at 45-50° C. for 4-5 hours to obtain the acyl chloride product 1; adding the surface-containing amino group-containing nano-barium titanate and potassium carbonate to dimethyl sulfoxide to obtain a mixed solution a, and then adding the acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution b, and adding the mixed solution b dropwise to the mixed solution a in an ice-water bath. After the addition is completed, the temperature is raised to 40-45° C., and the reaction is stirred at a constant temperature for 10-11 hours to obtain a modified PTC material;
[0036] Further, the dosage ratio of the carboxyl product, DMF, and dichlorothionyl is 42-46 g: 120-130 mL: 13-15 g; the dosage ratio of the surface amino-containing nano-barium titanate, potassium carbonate, and dimethyl sulfoxide in the mixed solution a is 8-10 g: 0.01-0.02 mol: 60-70 mL; the dosage ratio of the acyl chloride product 1 and dimethyl sulfoxide in the mixed solution b is 45-47 g: 90-100 mL; the dosage ratio of the mixed solution a and the mixed solution b is 70-80 mL: 100-110 mL;
[0037] During the reaction of step B3, the carboxyl product reacts with thionyl chloride to generate an acyl chloride product 1; the amino group of the surface-containing nano-barium titanate reacts with the acyl chloride product 1 to load thiophene and DOPO on the nano-barium titanate, thereby obtaining a modified PTC material;
[0038] Beneficial effects of the invention: The invention discloses a composite current collector containing PTC material, comprising a polymer base film and copper metal layers located on the upper and lower surfaces of the polymer base film; the polymer base film is prepared from raw materials such as modified polypropylene, modified PTC material, lubricant, initiator and filler.
[0039] The modified polypropylene is obtained by grafting benzotriazole onto polypropylene and introducing epoxy groups at the same time; when benzotriazole contacts the surface of metal copper, it can form a stable complex with the surface of metal copper, thereby enhancing the binding force between the base film made of modified polypropylene and the surface of metal copper; these complexes can form a protective film to prevent the approach of corrosive media such as oxygen, water, acid, alkali, etc., and are also beneficial to the improvement of the corrosion resistance of the composite current collector; and the epoxy group can form a strong chemical bond with the metal surface, thereby further improving the adhesion between the polymer base film and the surface of metal copper, so that the polymer base film and the surface of metal copper are more closely bonded; the polymer base film made of modified polypropylene makes up for the defect of insufficient binding force between the polypropylene base film and the surface of metal copper, and is more conducive to improving the structural stability of the composite current collector.
[0040] The modified PTC material is obtained by grafting thiophene rings and DOPO onto nano-barium titanate; after modification, the agglomeration of nano-barium titanate is improved, and the dispersion in the matrix is more uniform. When the temperature in the battery increases, the resistance of the composite current collector can suddenly increase to interrupt the flow of current, which can more effectively improve the thermal runaway phenomenon and improve the thermal runaway resistance of the composite current collector; the thiophene ring can effectively absorb ultraviolet energy and convert it into low-energy heat energy for release, thereby reducing the aging effect of ultraviolet rays on modified polypropylene, and the stability of the thiophene ring loaded on the nano-barium titanate is improved, which can better improve the ultraviolet resistance of the modified composite current collector; DOPO is loaded on the nano-barium titanate, the compatibility of DOPO and modified polypropylene is increased and it is not easy to infiltrate and fail. When DOPO burns, the surface of the high-molecular polymer is dehydrated and degraded to form a carbon layer, and the phosphorus-containing derivatives produced at the same time cover the polymer surface, isolate the transfer of combustible gas and heat, prevent further combustion, and improve the flame retardancy of the polymer base film, thereby avoiding the fire hazard of the battery during use. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] A modified polypropylene, the preparation of which comprises the following steps:
[0044] Step A1, add 7-octenoic acid to DMF, add dichlorothionyl under stirring, reflux and stir at 40°C for 4h to obtain an acyl chloride product; then add 6-methyl-7-nitro-1H-benzo[D][1,2,3]triazole and potassium carbonate to dimethyl sulfoxide to obtain a mixed solution 1, and then add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution 2, and add the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath. After the addition is completed, the temperature is raised to 40°C, the mixture is stirred at a constant temperature for 8h, and the mixture is distilled under reduced pressure to obtain the product. The nitro product is obtained; the dosage ratio of 7-octenoic acid, DMF, and dichlorothionyl is 0.1 mol: 50 mL: 0.12 mol; the dosage ratio of 6-methyl-7-nitro-1H-benzo[D][1,2,3]triazole, potassium carbonate, and dimethyl sulfoxide in mixed solution 1 is 0.1 mol: 0.02 mol: 40 mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 13 g: 30 mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 50 mL: 40 mL;
[0045] Step A2, adding the nitro product to ethyl acetate, heating to 45°C, starting reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 1 hour to obtain a primary amine product; the amount ratio of the nitro product, ethyl acetate, and sodium dithionite is 32g:100mL:18g;
[0046] Step A3, adding epichlorohydrin, primary amine product and tetrabutylammonium bromide to toluene, reflux stirring and reacting at 100°C for 3h, adding sodium hydroxide solution after cooling to room temperature, stirring for 5h, and obtaining a functional product; the dosage ratio of epichlorohydrin, primary amine product, tetrabutylammonium bromide, toluene and sodium hydroxide solution is 19g:35g:0.05mol:90mL:20mL; the mass fraction of sodium hydroxide solution is 40%;
[0047] Step A4: In a nitrogen atmosphere, the functional product and divinylbenzene were added to toluene, stirred for 10 min, and then polypropylene (supplier: Shanghai Oushuo Plastic Co., Ltd.) was added and stirred for 10 min. The reaction bottle was sealed and then heated to 400 °C. 60 After irradiation with Coγ rays for 8 hours, the product was taken out and then rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified polypropylene; the dosage ratio of toluene, functional product, divinylbenzene and polypropylene was 450mL:40g:7g:130g.
[0048] Example 2
[0049] A modified polypropylene, the preparation of which comprises the following steps:
[0050] Step A1, add 5-methylhexyl-2-butenoic acid to DMF, add dichlorothionyl under stirring, reflux and stir at 45°C for 4.5h to obtain an acyl chloride product; then add 4-nitro-1H-1,2,3-benzotriazole and potassium carbonate to dimethyl sulfoxide to obtain a mixed solution 1, and then add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution 2, and add the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath. After the addition is completed, the temperature is raised to 42°C, the mixture is stirred at a constant temperature for 9h, and the mixture is distilled under reduced pressure. The nitro product is obtained; the dosage ratio of 5-methylhexyl-2-butenoic acid, DMF, and dichlorothionyl is 0.11 mol: 55 mL: 0.13 mol; the dosage ratio of 4-nitro-1H-1,2,3-benzotriazole, potassium carbonate, and dimethyl sulfoxide in mixed solution 1 is 0.13 mol: 0.03 mol: 45 mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 14 g: 35 mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 55 mL: 45 mL;
[0051] Step A2, adding the nitro product to ethyl acetate, heating to 50°C, starting reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 1.3h to obtain a primary amine product; the amount ratio of the nitro product, ethyl acetate, and sodium dithionite is 34g:105mL:19g;
[0052] Step A3, adding epichlorohydrin, primary amine product and tetrabutylammonium bromide to toluene, reflux stirring and reacting at 105°C for 3.5 hours, adding sodium hydroxide solution after cooling to room temperature, stirring for 5.5 hours, and obtaining a functional product; the amount ratio of epichlorohydrin, primary amine product, tetrabutylammonium bromide, toluene and sodium hydroxide solution is 20g:37g:0.065mol:95mL:23mL; the mass fraction of sodium hydroxide solution is 45%;
[0053] Step A4: In a nitrogen atmosphere, the functional product and divinylbenzene were added to toluene, stirred for 13 min, polypropylene (supplier: Shanghai Oushuo Plastic Co., Ltd.) was added, and stirring was continued for 13 min. The reaction bottle was sealed and then 60 After irradiation with Coγ rays for 9 hours, the product was taken out and then rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified polypropylene; the dosage ratio of toluene, functional product, divinylbenzene and polypropylene was 475mL:45g:8g:135g.
[0054] Example 3
[0055] A modified polypropylene, the preparation of which comprises the following steps:
[0056] Step A1, 5-hexenoic acid is added to DMF, and dichlorothionyl is added under stirring, and the mixture is refluxed and stirred at 50°C for 5 hours to obtain an acyl chloride product; then 4-nitro-1H-1,2,3-benzotriazole and potassium carbonate are added to dimethyl sulfoxide to obtain a mixed solution 1, and then the acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2. In an ice-water bath, the mixed solution 2 is added dropwise to the mixed solution 1. After the addition is completed, the temperature is raised to 45°C, the mixture is stirred at a constant temperature for 10 hours, and the mixture is distilled under reduced pressure to obtain to the nitro product; the dosage ratio of 5-hexenoic acid, DMF, and dichlorothionyl is 0.12mol:60mL:0.15mol; the dosage ratio of 4-nitro-1H-1,2,3-benzotriazole, potassium carbonate, and dimethyl sulfoxide in mixed solution 1 is 0.15mol:0.04mol:50mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide in mixed solution 2 is 16g:40mL; the dosage ratio of mixed solution 1 and mixed solution 2 is 60mL:50mL;
[0057] Step A2, adding the nitro product to ethyl acetate, heating to 55°C, starting reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 1.5h to obtain a primary amine product; the amount ratio of the nitro product, ethyl acetate, and sodium dithionite is 36g:110mL:20g;
[0058] Step A3, adding epichlorohydrin, primary amine product and tetrabutylammonium bromide to toluene, reflux stirring and reacting at 110°C for 4 hours, adding sodium hydroxide solution after cooling to room temperature, stirring for 6 hours, and obtaining a functional product; the dosage ratio of epichlorohydrin, primary amine product, tetrabutylammonium bromide, toluene and sodium hydroxide solution is 21g:39g:0.08mol:100mL:25mL; the mass fraction of the sodium hydroxide solution is 50%;
[0059] Step A4: In a nitrogen atmosphere, the functional product and divinylbenzene were added to toluene, stirred for 15 min, and then polypropylene (supplier: Shanghai Oushuo Plastic Co., Ltd.) was added and stirred for 15 min. The reaction bottle was sealed and then heated to 400 °C. 60 After irradiation with Coγ-rays for 10 hours, the mixture was taken out and then rinsed with anhydrous ethanol, extracted with acetone and dried to obtain modified polypropylene; the dosage ratio of toluene, functional product, divinylbenzene and polypropylene was 500mL:50g:9g:140g.
[0060] Example 4
[0061] A modified PTC material, the preparation of which comprises the following steps:
[0062] Step B1, adding KH-550 to ethanol and deionized water, stirring for 8 hours to obtain a hydrolyzate; then adding nano-barium titanate to ethanol, ultrasonically dispersing for 20 minutes to obtain a dispersion; heating to 60°C, adding the hydrolyzate dropwise to the dispersion under ultrasound, stirring for 10 hours, and then drying and grinding into powder to obtain nano-barium titanate containing amino groups on the surface; the amount ratio of KH-550, ethanol and deionized water in the hydrolyzate is 10g:60mL:35mL; the amount ratio of nano-barium titanate and ethanol in the dispersion is 5g:100mL; the amount ratio of hydrolyzate and dispersion is 40mL:115mL; the volume fraction of ethanol is 95%;
[0063] Step B2, in a nitrogen atmosphere, add 2-thiophenecarboxaldehyde to acetic anhydride, then add potassium carbonate, reflux and react at 150°C with stirring for 24h, extract, rotary evaporate and dry to obtain an unsaturated carboxylic acid; in a nitrogen atmosphere, add DOPO and unsaturated carboxylic acid to DMF, stir and react at 90°C for 8h, cool to room temperature, recrystallize in an ice-water bath, and filter under reduced pressure to obtain a carboxyl product; the dosage ratio of 2-thiophenecarboxaldehyde, acetic anhydride and potassium carbonate is 0.1mol:0.05mol:5mmol; the dosage ratio of DOPO, unsaturated carboxylic acid and DMF is 23g:16g:80mL;
[0064] Step B3, the carboxyl product is added to DMF, and dichlorothionyl is added under stirring, and the reaction is refluxed and stirred at 45 ° C for 4 hours to obtain the acyl chloride product 1; the surface-containing amino-containing nano-barium titanate and potassium carbonate are added to dimethyl sulfoxide to obtain a mixed solution a, and then the acyl chloride product 1 is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a under an ice water bath. After the addition is completed, the temperature is raised to 40 ° C, and the reaction is stirred at a constant temperature for 10 hours to obtain a modified PTC material; the amount ratio of the carboxyl product, DMF, and dichlorothionyl is 42g:120mL:13g; the amount ratio of the surface-containing amino-containing nano-barium titanate, potassium carbonate and dimethyl sulfoxide in the mixed solution a is 8g:0.01mol:60mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide in the mixed solution b is 45g:90mL; the amount ratio of the mixed solution a and the mixed solution b is 70mL:100mL.
[0065] Example 5
[0066] A modified PTC material, the preparation of which comprises the following steps:
[0067] Step B1, adding KH-540 to ethanol and deionized water, stirring for 9 hours to obtain a hydrolyzate; then adding nano-barium titanate to ethanol, ultrasonically dispersing for 25 minutes to obtain a dispersion; heating to 65°C, adding the hydrolyzate dropwise to the dispersion under ultrasound, stirring for 10.5 hours, and then drying and grinding into powder to obtain nano-barium titanate containing amino groups on the surface; the amount ratio of KH-540, ethanol and deionized water in the hydrolyzate is 11g:65mL:40mL; the amount ratio of nano-barium titanate and ethanol in the dispersion is 5.5g:110mL; the amount ratio of hydrolyzate and dispersion is 45mL:120mL; the volume fraction of ethanol is 95%;
[0068] Step B2, in a nitrogen atmosphere, 2,2-bithiophene-5-acetaldehyde was added to acetic anhydride, and potassium carbonate was added, and the mixture was refluxed and stirred at 160°C for 25 hours, and the unsaturated carboxylic acid was obtained by extraction, rotary evaporation, and drying; in a nitrogen atmosphere, DOPO and the unsaturated carboxylic acid were added to DMF, and the mixture was stirred and reacted at 100°C for 9 hours, and the mixture was cooled to room temperature, recrystallized in an ice-water bath, and filtered under reduced pressure to obtain a carboxyl product; the dosage ratio of 2,2-bithiophene-5-acetaldehyde, acetic anhydride, and potassium carbonate was 0.13 mol: 0.06 mol: 6.5 mmol; the dosage ratio of DOPO, the unsaturated carboxylic acid, and DMF was 25 g: 19 g: 90 mL;
[0069] Step B3, the carboxyl product is added to DMF, and dichlorothionyl is added under stirring, and the reaction is refluxed and stirred at 47 ° C for 4.5 hours to obtain the acyl chloride product 1; the surface-containing amino-containing nano-barium titanate and potassium carbonate are added to dimethyl sulfoxide to obtain a mixed solution a, and then the acyl chloride product 1 is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a under an ice water bath. After the addition is completed, the temperature is raised to 42 ° C, and the reaction is stirred at a constant temperature for 10.5 hours to obtain a modified PTC material; the amount ratio of the carboxyl product, DMF, and dichlorothionyl is 44g:125mL:14g; the amount ratio of the surface-containing amino-containing nano-barium titanate, potassium carbonate and dimethyl sulfoxide in the mixed solution a is 9g:0.015mol:65mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide in the mixed solution b is 46g:95mL; the amount ratio of the mixed solution a and the mixed solution b is 75mL:105mL.
[0070] Example 6
[0071] A modified PTC material, the preparation of which comprises the following steps:
[0072] Step B1, adding N-methyl-3-aminopropyltrimethoxysilane to ethanol and deionized water, stirring for 10 hours to obtain a hydrolyzate; then adding nano-barium titanate to ethanol, ultrasonically dispersing for 30 minutes to obtain a dispersion; heating to 70°C, adding the hydrolyzate dropwise to the dispersion under ultrasound, stirring for 11 hours, and then drying and grinding into powder to obtain nano-barium titanate containing amino groups on the surface; the amount ratio of N-methyl-3-aminopropyltrimethoxysilane, ethanol and deionized water in the hydrolyzate is 12g:70mL:45mL; the amount ratio of nano-barium titanate and ethanol in the dispersion is 6g:120mL; the amount ratio of hydrolyzate to dispersion is 50mL:125mL; the volume fraction of ethanol is 95%;
[0073] Step B2, in a nitrogen atmosphere, 5-isobutylthiophene-2-carboxaldehyde was added to acetic anhydride, and potassium carbonate was added, and the mixture was refluxed and stirred at 170°C for 26 hours, and the unsaturated carboxylic acid was obtained by extraction, rotary evaporation, and drying; in a nitrogen atmosphere, DOPO and the unsaturated carboxylic acid were added to DMF, and the mixture was stirred and reacted at 110°C for 10 hours, and the mixture was cooled to room temperature, recrystallized in an ice-water bath, and filtered under reduced pressure to obtain a carboxyl product; the dosage ratio of 5-isobutylthiophene-2-carboxaldehyde, acetic anhydride, and potassium carbonate was 0.15 mol: 0.07 mol: 8 mmol; the dosage ratio of DOPO, unsaturated carboxylic acid, and DMF was 27 g: 22 g: 100 mL;
[0074] Step B3, the carboxyl product is added to DMF, and dichlorothionyl is added under stirring, and the reaction is refluxed and stirred at 50°C for 5h to obtain the acyl chloride product 1; the surface-containing amino-containing nano-barium titanate and potassium carbonate are added to dimethyl sulfoxide to obtain a mixed solution a, and then the acyl chloride product 1 is added to dimethyl sulfoxide to obtain a mixed solution b, and the mixed solution b is added dropwise to the mixed solution a under an ice-water bath. After the addition is completed, the temperature is raised to 45°C, and the reaction is stirred at a constant temperature for 11h to obtain a modified PTC material; the amount ratio of the carboxyl product, DMF, and dichlorothionyl is 46g:130mL:15g; the amount ratio of the surface-containing amino-containing nano-barium titanate, potassium carbonate, and dimethyl sulfoxide in the mixed solution a is 10g:0.02mol:70mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide in the mixed solution b is 47g:100mL; the amount ratio of the mixed solution a and the mixed solution b is 80mL:110mL.
[0075] Example 7
[0076] A composite current collector containing a PTC material, comprising a polymer base film and copper metal layers located on the upper and lower surfaces of the polymer base film; the polymer base film comprises the following raw materials in parts by weight: 100 parts of modified polypropylene, 20 parts of modified PTC material, 1.2 parts of lubricant, 0.3 parts of initiator, and 14 parts of filler; the lubricant is butyl stearate; the initiator is diisopropylbenzene peroxide; the filler is alkali-free glass fiber (supplier: Hebei Jiegui Mineral Products Co., Ltd.);
[0077] The preparation of the composite current collector containing the PTC material comprises the following steps:
[0078] Step S1, stirring the modified polypropylene obtained in Example 1, the modified PTC material obtained in Example 4, the lubricant, the initiator and the filler for 30 minutes, extruding through a twin-screw extruder at 220° C., stretching at 115° C., heat-setting at 230° C. to form a film, then soaking in distilled water at 55° C. for 10 hours, and finally drying at 90° C. for 6 hours to obtain a polymer base film;
[0079] Step S2, using a vacuum evaporation method, the polymer base film is passed through the copper plating roller along the axial direction of the copper plating roller, and the evaporated metal copper is plated on both sides of the polymer base film to obtain a composite current collector containing PTC material; the copper plating roller has a first temperature zone and a second temperature zone, the temperature of the first temperature zone is 45°C, and the temperature of the second temperature zone is 15°C.
[0080] Example 8
[0081] A composite current collector containing a PTC material, comprising a polymer base film and copper metal layers located on the upper and lower surfaces of the polymer base film; the polymer base film comprises the following raw materials in parts by weight: 105 parts of modified polypropylene, 23 parts of modified PTC material, 1.3 parts of lubricant, 0.4 parts of initiator, and 16 parts of filler; the lubricant is butyl stearate; the initiator is diisopropylbenzene peroxide; the filler is alkali-free glass fiber (supplier: Hebei Jiegui Mineral Products Co., Ltd.);
[0082] The preparation of the composite current collector containing the PTC material comprises the following steps:
[0083] Step S1, stirring the modified polypropylene obtained in Example 2, the modified PTC material obtained in Example 5, the lubricant, the initiator and the filler for 35 minutes, extruding through a twin-screw extruder at 230° C., stretching at 120° C., heat-setting at 235° C. to form a film, then soaking in distilled water at 60° C. for 10.5 hours, and finally drying at 95° C. for 7 hours to obtain a polymer base film;
[0084] Step S2: using a vacuum evaporation method, the polymer base film is passed through a copper plating roller along the axial direction of the copper plating roller, and the evaporated metal copper is plated on both sides of the polymer base film to obtain a composite current collector containing a PTC material; the copper plating roller has a first temperature zone and a second temperature zone, the temperature of the first temperature zone is 50°C, and the temperature of the second temperature zone is 20°C.
[0085] Example 9
[0086] A composite current collector containing a PTC material, comprising a polymer base film and copper metal layers located on the upper and lower surfaces of the polymer base film; the polymer base film comprises the following raw materials in parts by weight: 110 parts of modified polypropylene, 25 parts of modified PTC material, 1.4 parts of lubricant, 0.5 parts of initiator, and 18 parts of filler; the lubricant is butyl stearate; the initiator is diisopropylbenzene peroxide; the filler is alkali-free glass fiber (supplier: Hebei Jiegui Mineral Products Co., Ltd.);
[0087] The preparation of the composite current collector containing the PTC material comprises the following steps:
[0088] Step S1, stirring the modified polypropylene obtained in Example 3, the modified PTC material obtained in Example 6, the lubricant, the initiator and the filler for 40 minutes, extruding them through a twin-screw extruder at 240° C., stretching them at 125° C., heat-setting them at 240° C. to form a film, then soaking them in distilled water at 65° C. for 11 hours, and finally drying them at 100° C. for 8 hours to obtain a polymer base film;
[0089] Step S2: using a vacuum evaporation method, the polymer base film is passed through a copper plating roller along the axial direction of the copper plating roller, and the evaporated metal copper is plated on both sides of the polymer base film to obtain a composite current collector containing a PTC material; the copper plating roller has a first temperature zone and a second temperature zone, the temperature of the first temperature zone is 55°C, and the temperature of the second temperature zone is 25°C.
[0090] Comparative Example 1
[0091] Compared with Example 9, the functional product used in the preparation process of modified polypropylene was replaced with functional product s, no epoxy group was introduced, benzotriazole was grafted into polypropylene, and the rest was completely the same as Example 9 to obtain a composite current collector containing PTC material;
[0092] The preparation process of functional product s is as follows:
[0093] Step A1, add 5-hexenoic acid to DMF, add dichlorothionyl under stirring, reflux and stir at 50°C for 5h to obtain acyl chloride product e; then add benzotriazole and potassium carbonate to dimethyl sulfoxide to obtain a mixed solution c, then add the acyl chloride product e to dimethyl sulfoxide to obtain a mixed solution d, add the mixed solution d dropwise to the mixed solution c under an ice-water bath, after the addition is complete, heat to 45°C, stir and react at a constant temperature for 10h, and distill under reduced pressure to obtain a functional product s; the dosage ratio of 5-hexenoic acid, DMF, and dichlorothionyl is 0.12mol:60mL:0.15mol; the dosage ratio of benzotriazole, potassium carbonate, and dimethyl sulfoxide is 0.1mol:0.02mol:40mL; the dosage ratio of acyl chloride product e and dimethyl sulfoxide is 16g:40mL; the dosage ratio of mixed solution c and mixed solution d is 60mL:50mL.
[0094] Comparative Example 2
[0095] Compared with Example 9, the nitro-containing benzotriazole used in the preparation of the modified polypropylene was replaced with N-methyl-3-nitrobenzylamine, that is, benzotriazole was not introduced, and the rest was exactly the same as Example 9 to obtain a composite current collector containing a PTC material.
[0096] Comparative Example 3
[0097] Compared with Example 9, the formaldehyde containing thiophene ring in the preparation process of the modified PTC material is replaced with p-methoxybenzaldehyde, that is, the thiophene ring is not supported on the nano-barium titanate, and the rest is exactly the same as Example 9 to obtain a composite current collector containing PTC material.
[0098] Comparative Example 4
[0099] Compared with Example 9, the carboxyl product in step B3 during the preparation of the modified PTC material is replaced with the unsaturated carboxylic acid obtained in step B2, i.e. DOPO is not loaded on nano-barium titanate, and the rest is exactly the same as in Example 9 to obtain a composite current collector containing PTC material.
[0100] Comparative Example 5
[0101] Compared with Example 9, the modified PTC material used was replaced with nano-barium titanate, and the rest was exactly the same as Example 9 to obtain a composite current collector containing the PTC material.
[0102] The following is a further effect test of the composite current collector containing PTC material prepared by the present invention, as follows:
[0103] Adhesion: A layer of Permacel P-94 double-sided tape is bonded to a 1 mm thick copper foil, a composite current collector is bonded on top of the double-sided tape, and a layer of ethylene acrylic acid copolymer film (DuPont Nurcel0903, 50 μm thick) is covered on top of the composite current collector. Then, the composite current collector is tested at 1.3 × 105 N / m 2 , hot pressing at 120°C for 10s, cooling to room temperature, and cutting into small strips of 150mm×15mm; finally, the ethylene acrylic acid copolymer film of the sample strip is fixed to the upper fixture of the tensile machine, and the rest is fixed to the lower fixture. After fixing, the two are peeled at an angle of 180° and a speed of 100mm / min to test the peeling force, which is the bonding force between the film and the metal conductive layer;
[0104] Corrosion resistance: A slurry obtained by mixing active material (graphite), conductive agent (conductive carbon black) and binder (sodium carboxymethyl cellulose) in a mass ratio of 94:3:3 was evenly coated on the surface of the composite current collector containing the PTC material, and the battery pole piece was obtained after drying at 100°C for 1-1.5 hours. The battery pole piece was immersed in a 1 mol / L LiPF6 EC / DMC / DEC mixed solution for 60 hours. The mass ratio of EC, DMC and DEC in the mixed solution was 1:2:1, and the corrosion phenomenon was observed;
[0105] Flame retardancy: flame retardancy test is carried out with reference to UL94 standard;
[0106] Tensile strength: For the polymer base film used in the composite current collector, the tensile strength test was carried out according to GB / T13022-1991, and the polymer base film was placed under ultraviolet radiation with an intensity of 0.89W / m 2 , after treatment at 25°C and aging time of 48h, the tensile strength retention rate was measured;
[0107] Thermal runaway performance: The composite current collector is used in a lithium-ion battery according to conventional technical means in the art, and the prepared lithium-ion battery is subjected to a needle puncture safety test with reference to the test method described in GB / T31485-2015, and the temperature of the corresponding lithium-ion battery after needle puncture is recorded. The results are recorded in Table 1;
[0108] Table 1: Test results
[0109]
[0110] According to the data in Table 1, the polymer base film of the composite current collector containing PTC material of the present invention has excellent adhesion to the copper metal layer, the polymer base film has good resistance to ultraviolet aging, and the composite current collector has strong corrosion resistance, flame retardancy and thermal runaway resistance. Comparison of Example 9 with Comparative Example 1 shows that the adhesion between the polymer base film of the composite current collector and the copper metal layer is reduced by only grafting benzotriazole into polypropylene to obtain modified polypropylene 1 without introducing epoxy groups. Comparison of Example 9 with Comparative Example 2 shows that without introducing benzotriazole, only introducing epoxy groups into polypropylene, not only the adhesion between the polymer base film of the composite current collector and the copper metal layer is reduced, but also the corrosion resistance of the composite current collector is reduced. Comparison of Example 9 with Comparative Example 3 shows that the thiophene ring is not loaded on nano-barium titanate, the anti-ultraviolet aging resistance of the polymer base film of the composite current collector obtained is reduced, and the anti-ultraviolet property of the composite current collector is reduced. Comparison between Example 9 and Comparative Example 4 shows that DOPO is not loaded on nano-barium titanate, the flame retardant grade of the obtained polymer base film decreases, and the flame retardancy of the composite current collector decreases. Comparison between Example 9 and Comparative Example 5 shows that without modifying the nano-barium titanate, the agglomeration phenomenon is not improved, the dispersion in the polymer base film is poor, resulting in a decrease in needle puncture safety, a decrease in the thermal runaway performance of the composite current collector, and the thiophene ring and DOPO are not loaded in the nano-barium titanate, the UV resistance and flame retardancy of the composite current collector decrease.
[0111] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A composite current collector containing a PTC material, characterized in that: It comprises a polymer base film and copper metal layers located on the upper and lower surfaces of the polymer base film; the polymer base film comprises the following raw materials in parts by weight: 100-110 parts of modified polypropylene, 20-25 parts of modified PTC material, 1.2-1.4 parts of lubricant, 0.3-0.5 parts of initiator, and 14-18 parts of filler; The modified polypropylene is prepared by the following steps: Step A1, adding a carboxylic acid containing a terminal carbon-carbon double bond to DMF, and reacting with dichlorothionyl with stirring to obtain an acyl chloride product; then adding nitro-containing benzotriazole and potassium carbonate to dimethyl sulfoxide to obtain a mixed solution 1, and then adding the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution 2, and in an ice-water bath, adding the mixed solution 2 dropwise to the mixed solution 1, and reacting with stirring to obtain a nitro product; Step A2, adding the nitro product to ethyl acetate, and stirring with sodium dithionite to react to obtain a primary amine product; Step A3, adding epichlorohydrin, primary amine product and tetrabutylammonium bromide into toluene, stirring for reaction, then adding sodium hydroxide solution, stirring for reaction to obtain a functional product; Step A4: In a protective gas atmosphere, the functional product and the cross-linking agent are added to toluene, and then polypropylene is added. 60 Modified polypropylene was obtained by Coγ-ray irradiation reaction.
2. A composite current collector containing a PTC material according to claim 1, characterized in that: The lubricant is selected from one of butyl stearate and ethylene bisstearamide, the initiator is dicumyl peroxide, and the filler is alkali-free glass fiber; in step A1, the amount ratio of carboxylic acid containing a terminal carbon-carbon double bond, DMF, and dichlorothionyl is 0.1-0.12 mol: 50-60 mL: 0.12-0.15 mol, and the carboxylic acid containing a terminal carbon-carbon double bond is selected from one of 7-octenoic acid, 5-methylhexyl-2-butenoic acid and 5-hexenoic acid.
3. The composite current collector containing a PTC material according to claim 1, characterized in that: In step A1, the amount ratio of the nitro-containing benzotriazole, potassium carbonate and dimethyl sulfoxide in the mixed solution 1 is 0.1-0.15 mol: 0.02-0.04 mol: 40-50 mL, and the nitro-containing benzotriazole is selected from 6-methyl-7-nitro-1H-benzo[D][1,2,3]triazole and 4-nitro-1H-1,2,3-benzotriazole; the amount ratio of the acyl chloride product and dimethyl sulfoxide in the mixed solution 2 is 13-16 g: 30-40 mL; the amount ratio of the mixed solution 1 and the mixed solution 2 is 50-60 mL: 40-50 mL.
4. The composite current collector containing a PTC material according to claim 1, characterized in that: In step A2, the usage ratio of the nitro product, ethyl acetate and sodium dithionite is 32-36 g: 100-110 mL: 18-20 g; in step A4, the usage ratio of toluene, functional product, cross-linking agent and polypropylene is 450-500 mL: 40-50 g: 7-9 g: 130-140 g, and the cross-linking agent is divinylbenzene.
5. The composite current collector containing a PTC material according to claim 1, characterized in that: In step A3, the usage ratio of epichlorohydrin, primary amine product, tetrabutylammonium bromide, toluene and sodium hydroxide solution is 19-21 g: 35-39 g: 0.05-0.08 mol: 90-100 mL: 20-25 mL; the mass fraction of the sodium hydroxide solution is 40-50%.
6. The composite current collector containing a PTC material according to claim 1, characterized in that: The preparation of the modified PTC material comprises the following steps: Step B1, adding an amino-containing silane coupling agent to ethanol and deionized water, stirring for 8-10 hours to obtain a hydrolyzate; then adding nano-barium titanate to ethanol, ultrasonically dispersing for 20-30 minutes to obtain a dispersion; heating to 60-70° C., adding the hydrolyzate dropwise to the dispersion under ultrasound, stirring for reaction for 10-11 hours, and then drying and grinding into powder to obtain nano-barium titanate containing amino groups on the surface; Step B2, in a protective gas atmosphere, add formaldehyde containing a thiophene ring to acetic anhydride, then add potassium carbonate, reflux and stir at 150-170° C. for 24-26 hours, extract, rotary evaporate, and dry to obtain an unsaturated carboxylic acid; in a protective gas atmosphere, add DOPO and the unsaturated carboxylic acid to DMF, stir and react at 90-110° C. for 8-10 hours, cool to room temperature, recrystallize in an ice-water bath, and filter under reduced pressure to obtain a carboxyl product; Step B3, add the carboxyl product to DMF, add dichlorothionyl under stirring, reflux and react at 45-50°C with stirring for 4-5h to obtain the acyl chloride product 1; add nano-barium titanate and potassium carbonate containing amino groups on the surface to dimethyl sulfoxide to obtain a mixed solution a, and then add the acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution b, and add the mixed solution b dropwise to the mixed solution a in an ice water bath. After the addition is completed, the temperature is raised to 40-45°C, and the reaction is stirred at a constant temperature for 10-11h to obtain a modified PTC material.
7. The composite current collector containing a PTC material according to claim 6, characterized in that: In step B1, the amount ratio of the amino-containing silane coupling agent, ethanol and deionized water in the hydrolyzate is 10-12g:60-70mL:35-45mL, and the amino-containing silane coupling agent is selected from one of KH-550, KH-540, N-methyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltrimethoxysilane; the amount ratio of nano-barium titanate and ethanol in the dispersion is 5-6g:100-120mL; the amount ratio of the hydrolyzate and the dispersion is 40-50mL:115-125mL; the volume fraction of ethanol is 95%.
8. The composite current collector containing a PTC material according to claim 6, characterized in that: In step B2, the amount ratio of formaldehyde containing a thiophene ring, acetic anhydride, and potassium carbonate is 0.1-0.15 mol: 0.05-0.07 mol: 5-8 mmol, and the formaldehyde containing a thiophene ring is selected from one of 2-thiophenecarboxaldehyde, 2,2-bithiophene-5-acetaldehyde, and 5-isobutylthiophene-2-carboxaldehyde; the amount ratio of DOPO, unsaturated carboxylic acid, and DMF is 23-27 g: 16-22 g: 80-100 mL.
9. The composite current collector containing a PTC material according to claim 6, characterized in that: In step B3, the amount ratio of the carboxyl product, DMF, and dichlorothionyl is 42-46 g: 120-130 mL: 13-15 g; the amount ratio of the surface amino-containing nano-barium titanate, potassium carbonate, and dimethyl sulfoxide in the mixed solution a is 8-10 g: 0.01-0.02 mol: 60-70 mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide in the mixed solution b is 45-47 g: 90-100 mL; the amount ratio of the mixed solution a and the mixed solution b is 70-80 mL: 100-110 mL.
10. A method for preparing a composite current collector containing a PTC material according to any one of claims 1 to 9, characterized in that: The steps include: Step S1, stirring the modified polypropylene, modified PTC material, lubricant, initiator and filler for 30-40 minutes, extruding through a twin-screw extruder at 220-240° C., stretching at 115-125° C., heat-setting at 230-240° C. to form a film, then soaking in distilled water at 55-65° C. for 10-11 hours, and finally drying at 90-100° C. for 6-8 hours to obtain a polymer base film; Step S2, using a vacuum evaporation method, the polymer base film is passed through the copper plating roller along the axial direction of the copper plating roller, and the evaporated metal copper is plated on both sides of the polymer base film to obtain a composite current collector containing PTC material; the copper plating roller has a first temperature zone and a second temperature zone, the temperature of the first temperature zone is 45-55°C, and the temperature of the second temperature zone is 15-25°C.
Citation Information
Patent Citations
Current collector containing PTC coatings, and lithium ion battery containing current collector
CN108511761A
Modified polypropylene film and application thereof in composite current collector
CN118772540A
Stretch-resistant base film for composite current collector and preparation method of stretch-resistant base film
CN118772606A
Nonaqueous electrolyte secondary battery and method for producing the same
US20110159361A1
Polypropylene film and preparation method therefor, composite current collector, and use thereof
WO2024130774A1
Cited By
Nickel-titanium alloy reinforced nano silicon carbide composite ceramic material and preparation process thereof
CN120157484A
Composite copper foil and preparation method thereof
CN120554789A